188 Gender differences in head impact rate and mechanism in high school lacrosse. (3rd March 2020) - Patton, Declan; Huber, Colin; Lallo, Valerie; McDonald, Catherine; Arbogast, Kristy
Abstract : Background: There is debate as to whether protective headwear should be mandated in female lacrosse; however, a lack of quantitative evidence exists regarding the effectiveness of, and case for, protective headwear in female lacrosse. Objective: To compare head impacts in male and female lacrosse in terms of rate recorded by headband-mounted sensors and mechanism determined by video analysis. Design: Prospective cohort observational study. Setting: One season of suburban high school female (12 games) and male (15 games) lacrosse competition. Participants: Adolescent female (n=15) and male (n=33) lacrosse players. Main outcome measurements: Head impact rate as calculated by the number of video-confirmed head impacts above 16 g recorded by SIM-G (Triax Technologies) headband-mounted impact sensors divided by the number of player-games during one season. Mechanism of impact (i.e. player contact, fall, stick-to-head or ball-to-head) determined by detailed video analysis of sensor-recorded events. Results: For male lacrosse, 226 head impacts were recorded during 275 player-games for an impact rate of 0.82 impacts per player-game. The most common mechanism for head impacts to male lacrosse players was player contact (57%) followed by stick-to-head (27%), falls (15%) and ball-to-head (2%). For female lacrosse, 7 head impacts were recording during 152 player-games for an impact rate of 0.05 impacts per player-game. Of the seven head impacts to female lacrosse players, three were player contact (43%), three were stick-to-head (43%) and one was a fall (14%). Conclusions: The impact rate for female lacrosse players is less than 6% of the rate for male lacrosse players, which suggests that head impacts in female high school lacrosse are rare. However, nearly half of the head impacts in female lacrosse were stick-to-head, for which protective headwear may reduce the risk of injury. Therefore, further investigation of the association between head impact mechanism and injury in female lacrosse is required.